Whole brain, high resolution multiband spin-echo EPI fMRI at 7 T: a comparison with gradient-echo EPI using a color-word Stroop task. - Boyacioğlu, R; Schulz, J; Müller, N; Koopmans, P; Barth, M; Norris, D (Academic Press Inc., 2014)
A whole brain, multiband spin-echo (SE) echo planar imaging (EPI) sequence employing a high spatial (1.5 mm isotropic) and temporal (TR of 2 s) resolution was implemented at 7 T. Its overall performance (tSNR, sensitivity and CNR) was assessed and compared to a geometrically matched gradient-echo (GE) EPI multiband sequence (TR of 1.4 s) using a color-word Stroop task. PINS RF pulses were used for refocusing to reduce RF amplitude requirements and SAR, summed and phase-optimized standard pulses were used for excitation enabling a transverse or oblique slice orientation. The distortions were minimized with the use of parallel imaging in the phase encoding direction and a post-acquisition distortion correction. In general, GE-EPI shows higher efficiency and higher CNR in most brain areas except in some parts of the visual cortex and superior frontal pole at both the group and individual-subject levels. Gradient-echo EPI was able to detect robust activation near the air/tissue interfaces such as the orbito-frontal and subcortical regions due to reduced intra-voxel dephasing because of the thin slices used and high in-plane resolution.